Impact of Dietary Supplementation of Black Cumin Seed on Performance and Carcass Quality of Japanese Quail (Research in Agriculture Livestock and Fisheries, 2025)
The study aims to evaluate the impact of dietary supplementation of different levels of black cumin seed on performance and carcass characteristics of Japanese quail. The study included six treatments, T0 (basal diet), T1 (basal diet + 0.5% black cumin seed), T2 (basal diet + 1.0% black cumin seed), T3 (basal diet + 1.5% black cumin seed), T4 (basal diet + 2.0% black cumin seed), and T5 (basal diet + 2.5% black cumin seed). The 450 experimental Japanese quails were then distributed to six treatments with five replications (15 birds/replication). The BW, BWG, FC, FCR, and DP of quail on different treatments was recorded. From the study, significant (p